Implementasi Metode Dempster Shafer Dalam Diagnosis Penyakit Pada Tanaman Jeruk - Salam Maulana; Nurul Hidayat; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Citrus Plants is one of the national commodities that has an imporant role in increasing the country's foreign exchange. According to the data from Badan Litbang Pertanian Indonesia (2015), the increase imports of citrus by 11% anually in a span of a decade, makes Indonesia become a promising International markets. It should encourage farmers, especially citrus farmers to innovate in order to compete with imported goods. Many people are trying to cultivate citrus crops. However, it is not balanced with the knowledge of how to deal with crops diseasaes. There are many problems regarding citrus plants faced by farmers, one of which is pest problem that needs special attention, for it affects the production and cause diseases. In this research, the system was developed using Dempster-Shafer method as disease detector. The data were collected using interview related to theory. The results of this research is a plant disease-diagnostic system utilizing Demspter-Shafer method that detect simptom, cause, and solution; and it is based on theory of the experts. Based on the tests that had been done, it was found that the acuracy reached 90% that indicates the system was functioning properly using Dempster-shafer.